DESKRIPSI EKSPLORATIF ETNOMATEMATIKA DALAM PERMAINAN TRADISIONAL LOMPAT TALI DI KUBU RAYA - Aulia, Hafidzo; Rustam, Rustam; Fitriawan, Dona (Universitas Tanjungpura, 2023)
This research aims to describe the concept of mathematics, ethnomathematics, and to form learner worksheet through the traditional game of jumping rope. The method used in this research is descriptive method with ethnographic approach. Research data were obtained from observations and interviews. The results showed the existence of mathematical concepts including circles in the form of game tools, straight lines appear when weaving rubber bands, opportunities appear when determining the order of play, counting appears when the guard counts 1 until 10, rectangles appear when two guards hold the rubber rope, triangles appear when players form roofs, trapezoids appear when players form houses, rhombuses appear when players form rhombuses, and kites appear when players form kites. And there are six characteristics of ethnomathematics including counting (counting the number of players in the traditional game of jumping rope), measuring (determining the order of play in the traditional game of jumping rope), designing (making traditional game tools jump rope), locating (position when playing the traditional game of jumping rope), playing (the existence of procedures/rules for playing the traditional game of jumping rope), and explaining (explaining stories about the course of the game, the time when playing, and related mathematical material in the traditional game of jumping rope).